THE GOLDEN PROPORTION AND LOWER LIMB ALIGNMENT (GYMNASIUM, 2009)
The study undertaken aimed to highlight the link between the golden proportion and alignment of thelower limb, especially the foot, also finding a means for rapid assessment of foot position by using a tool thatallows a rapid diagnosis of deviations, useful in practice, in the work of a physical therapist.The golden proportion, the result of golden section, in which the whole is divided into two unequalparts, so that the large part is mean proportional between the small part and whole, is found in the structureof the human body or in the structure of various parts of human body.